Possibilities of using the assumptions of positive psychology in the process of preparing children to cope with crisis situations - Janina Uszyńska-Jarmoc; Małgorzata Głoskowska-Sołdatow (Studia z Teorii Wychowania)
The text presents the possibilities of using selected assumptions of positive psychology in the process of preparing students at a younger school age to cope with the civilization threats of the 21st century (pandemics, migrations, wars, hunger, etc.), understood as crises that can be learned to overcome. In the process of education, especially in early childhood, the issue of threats to civilization is usually ignored, e.g. therefore, there are more and more disturbing phenomena in the lives of children and adolescents (aggression, depression, withdrawal, etc.).The assumptions of positive psychology are presented and used in this text not as a starting point for designing therapeutic activities, but for designing preventive educational processes. The text also refers to the theory of self-determination (SDT) by E. Deci and R. Ryan, and in particular to one of its sub-theories relating to human needs and motivation. The need to ensure that the child in the education process meets the three most basic human needs: competences, relations with others and autonomy - treated as necessary conditions for children's well-being and learning to cope with crises that appear "here and now" and in the future.